Hydrogen‐Borrowing and Interrupted‐Hydrogen‐Borrowing Reactions of Ketones and Methanol Catalyzed by Iridium1. Issue 5 (9th December 2014) - Shen, Di; Poole, Darren L.; Shotton, Camilla C.; Kornahrens, Anne F.; Healy, Mark P.; Donohoe, Timothy J.
Abstract Reported herein is the use of catalytic [Ir(cod)Cl2] to facilitate hydrogen‐borrowing reactions of ketone enolates with methanol at 65 °C. An oxygen atmosphere accelerates the process, and when combined with the use of a bulky monodentate phosphine ligand, interrupts the catalytic cycle by preventing enone reduction. Subsequent addition of pro‐nucleophiles to the reaction mixture allowed a one‐pot methylenation/conjugate addition protocol to be developed, which greatly expands the range of products that can be made by this methodology.